Non-neutralizing antibodies to SARS-Cov-2-related linear epitopes induce psychotic-like behavior in mice - Xu, Jinming; Wei, Hui; You, Pengsheng; Sui, Jiaping; Xiu, Jianbo; Zhu, Wanwan; Xu, Qi (Frontiers in Molecular Neuroscience, 2023)
An increasing number of studies have reported that numerous patients with coronavirus disease 2019 (COVID-19) and vaccinated individuals have developed central nervous system (CNS) symptoms, and that most of the antibodies in their sera have no virus-neutralizing ability. We tested the hypothesis that non-neutralizing anti-S1-111 IgG induced by the spike protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) could negatively affect the CNS. After immunizing ApoE-/- mice with S1-111, an increased level of anti-S1-111 IgG was measured in their serum and brain homogenate. Importantly, anti-S1-111 IgG increased the density of microglia, activated microglia, and astrocytes in the hippocampus, and we observed a psychomotor-like behavioral phenotype with defective sensorimotor gating and impaired spontaneity among S1-111-immunized mice. Transcriptome profiling showed that up-regulated genes in S1-111-immunized mice were mainly associated with synaptic plasticity and mental disorders. Overall, our results show that the non-neutralizing antibody anti-S1-111 IgG induced by the spike protein caused a series of psychotic-like changes in model mice by activating glial cells and modulating synaptic plasticity. Preventing the production of anti-S1-111 IgG (or other non-neutralizing antibodies) may be a potential strategy to reduce CNS manifestations in COVID-19 patients and vaccinated individuals.